An on-site and remote study during the COVID-19 pandemic on virtual hand appearance and tactile feedback. Issue 12 (10th September 2021) - Cui, Dixuan; Mousas, Christos
ABSTRACT: A virtual reality (VR) study was conducted both in our lab setting and remotely to investigate the effects of virtual hand appearance and tactile feedback on ownership, external appearance, and tactile sensation embodiment dimensions when participants were instructed to perform an assembly task in a virtual environment. Six experimental conditions that combine hand appearances (abstract, mannequin, and realistic) and tactile feedback (tactile and no tactile) levels were examined. The results of our study indicated that: (1) the more realistic hand had a stronger effect on tactile sensation and external appearance, while the mannequin hand was associated with a greater ownership effect; (2) tactile feedback was associated with a stronger effect on external appearance compared to no tactile feedback; (3) the realistic hand model in conjunction with tactile feedback significantly affected the tactile sensation of the participants; (4) the participants in the lab setting rated the external appearance of the realistic hand model higher than the remote participants; (5) the participants exposed for less than one hour per week to VR rated the tactile sensation in the presence of tactile feedback higher, while they similarly rated the external appearance of the virtual hand model in the presence of a realistic hand model higher when compared to those who were exposed for more than one hour per week to VR; and finally, (6) the younger participants rated the tactile sensation higher than the older participants in the presence of the realistic hand model. In this paper, we discuss our findings and provide design considerations for virtual reality applications that consider virtual hands and tactile feedback.